PROBLEMS OF EUROPEAN COMMODITY SECURITY AND SUSTAINABLE DEVELOPMENT OF THE CENTRAL ASIA-CAUCASUS REGION - TVALCHRELIDZE, Alexander; SILAGADZE, Avtandil (CENTRAL ASIA AND THE CAUCASUS, 2011)
The Russia-Ukraine “gas wars” and the cold winter that hit Southern and Central Europe in January 2006 and 20091 highlighted Europe’s commodity insecurity and its dependence on Russian good will. In all fairness, it should be noted that some studies on this topic appeared even before the “cold winter” of 2009,2 but their impact on the leadership of the European Commission was insignificant, to put it mildly. This is evident from the fact that prior to the 2009 crisis the International Energy Agency did not see any pitfalls in European energy security.3 The James A. Baker III Institute for Public Policy was much more far-sighted. Back in 2005 it already argued the need to reduce, as far as possible, Russia’s influence on the energy sector and developed a model for international trade in gas known as the Baker Institute World Gas Trade Model (BIWGTM).4 Thus, there is evidence of Europe’s commodity insecurity, and any international conflicts interrupting the steady flow of raw materials to this region can have grave consequences for the daily life of Europeans and the stability of their democratic governments